The effectiveness of patchouli oil as hand sanitizer: a comparative study between two antiseptic brands - Zinatul Hayati; Dedy Syahrizal; Nisrina Nurhikmah; Fauzul Husna; Wilda Mahdani; Ade Oktiviyari; Tjut Mariam Zanaria (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2022)
Introduction: Hand hygiene is a non-pharmacological intervention recommended worldwide to prevent and control infectious diseases. Hand sanitizer is an antiseptic that contains active agents and could eradicate pathogenic microorganisms caused by infectious diseases. The addition of patchouli oil as an active agent in hand sanitizers has been proven to have a bactericidal and bacteriostatic effect against bacteria and viruses. This study aims to compare Hand sanitizer A's effectiveness (which does not contain patchouli oil) with Hand sanitizer B (containing patchouli oil) by comparing the number of normal hand flora colonies before and after using both hand sanitizers. Methods: This study is a pre-experimental design with a static group pretest and posttest design. There were 16 Medical Laboratory Technologists (MLT) enrolled in the study. Each MLT received two interventions, using Hand sanitizer A and B. The hand swabs were collected before and after using both hand sanitizers. The swabs inoculated on the media, incubated, and colony-forming units were counted. Result: This study showed a significant difference between hand sanitizers containing and not containing patchouli oil in reducing the number of normal hand flora colonies with a p-value = 0.033 (α < 0.05). The median value of total colonies decreased in Hand sanitizer B is 15, lower than the median value of Hand sanitizer A, which is 36. Conclusion: Hand sanitizer B containing patchouli oil possessed preferable effects to Hand sanitizer A, which does not contain patchouli oil in reducing the number of normal hand flora colonies.